El mito de origen de Cusco en tres novelas colombianas contemporáneas (2012)
ABSTRACT: Since it was included in the chronicles, the myth of Cusco origin, especially the version set by Inca Garcilaso de la Vega in Comentarios Reales, has been subject of interest and rewriting in Latin American narrative. In the twentieth century, three Colombian novels with an indigenous subject use this myth as an element in speech and story, revealing both a contemporary form of mythical matter transformation and a literary interest to represent, in order to promote it, the traditional knowledge.